2010
DOI: 10.1108/17410381011077964
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation approach to evaluating assembly line balancing with variable operation times

Abstract: Purpose -The purpose of this paper is to develop a computer simulation model to evaluate the bowl phenomenon and the allocation at the end of the line of stations with either greater mean operation times or higher variability of operation times. Design/methodology/approach -The model was developed on the basis of a realistic case problem and applied to a six-station assembly line. The evaluation criteria were the: minimization of the total elapsed time; maximization of the average percentage of working time; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…In more recent studies the CV bowl pattern also showed better results in terms of IT (Das et al, 2010) and average buffer levels (ABL) (Shaaban and Hudson, 2009). De la Wyche and Wilde (1977), however, observed in an extensive study of three, four and 12 station lines with buffer capacity of zero or one, that for the shorter three and four station lines, slight reductions in IT were obtained for the bowl pattern over the balanced line, but that for the longer 12 station line however, ITs were significantly higher than for the control, suggesting that the superiority of the bowl pattern only existed for shorter lines.…”
Section: Introductionmentioning
confidence: 84%
“…In more recent studies the CV bowl pattern also showed better results in terms of IT (Das et al, 2010) and average buffer levels (ABL) (Shaaban and Hudson, 2009). De la Wyche and Wilde (1977), however, observed in an extensive study of three, four and 12 station lines with buffer capacity of zero or one, that for the shorter three and four station lines, slight reductions in IT were obtained for the bowl pattern over the balanced line, but that for the longer 12 station line however, ITs were significantly higher than for the control, suggesting that the superiority of the bowl pattern only existed for shorter lines.…”
Section: Introductionmentioning
confidence: 84%
“…Liu and Chen (2002) [10] presented a generic algorithm approach for work line balancing planning involving various objectives, such as minimizing cycle time, maximizing workload smoothness, minimizing the frequency of tool change, minimizing the number of tools and machines used and minimizing the complexity of assembly sequences. The traditional methods of work line balancing assumed that production task time is constant, which is not realistic [11]. In labour intensive production processes like the agro-industry, the task time is uncertain since it depends on the skill of each employee, work environment, fatigue [7] [12].…”
Section: The Concept Of Work Line Balancingmentioning
confidence: 99%
“…Furthermore, it should be noted that a balanced assembly line may not be compatible with maximum line utilization. Hillier and Boling [7] conducted several pioneering studies to make a comparison between balanced and unbalanced lines. In our research, in order to take into account the possible unbalancing benefits, we have developed a flexible algorithm in which we can fix the total operation time (t f ) for theJ-th station.…”
Section: Solution Algorithmmentioning
confidence: 99%